RETRACTED_A case study of pre-service teachers’ enabling TPACK knowledge: lesson design projects - Agustina Tyarakanita; Endah Kurtianti; Endang Fauziati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
Retraction NoticeLeksika, Vol.14, No.2, August 2020Purwokerto, September 11, 2020  First Published August 21 , 2020  Article Information Original Article:http://jurnalnasional.ump.ac.id/index.php/LEKSIKA/article/view/7374 AbstractAt the request of the Journal Editor and the Publisher, the following article has been retracted.Agustina, T, et.al. 2020. A case study of pre-service teachers’ enabling TPACK knowledge: lesson design projects. Leksika Vol.14, No. 2, August 2020. Purwokerto: Faculty of Letters, Universitas Muhammadiyah Purwokerto. The article history in Leksika 12 May 2020        Tthe authors submitted the article.14 August 2020    Leksika sent its last review.17 August 2020    the authors submitted its final revision.18 August 2020   Editor notified the authors that the article was accepted.        21 August 2020    The article was published online. Juni 2020        The article has been published by another journal, ELS Journal on Interdisciplinary Studies in Humanities Vol 3, No. 2, June 202020 August 2020    The authors send an email requesting the retraction (cited below)